The Common Market: princes, competition and "harmonisation" - BERTRAND, R. (PSL Quarterly Review, 2014)
By abolishing barriers to international competition and facilitating the free movement of products and factors of production, the Common Market will undoubtedly have a profound influence on the mechanism of price determination in the Member States. This influence will be partly the result of automatic adjustments, and partly of actions by Member States and by the new common institutions. The present article is concerned with the powers vested in these common institutions. Under the terms of the Treaty, there are considerable powers of intervention in the field of prices. However, the provisions in this area are the products of a very mixed set of motives and two somewhat contradictory economic philosophies. On the one hand, there is faith, at least in the international sphere, in market forces and the mechanism of free competition. On the other hand, there is fear that adjustment of prices, costs of production factors and profit margins among the participating countries might involve serious disturbances, with some countries or industries suffering losses. A demand thus arrises for the “harmonisation” of these elements. JEL: F15, E31